Sarawak cuisine: an overview and its identity / Christopher Wan Sageng ... [et al.] - Wan Sageng, Christopher; Kasa, Mark; Pudun, Joseph Martin; Ramli, Nursyafiqah (UiTM Press, 2020)
It is without a doubt that gastronomic tourism is merging as one of the famous tourist areas of study. However, little research has been conducted on ethnic food and tourism in Southeast Asia. In particular, there is a lack of information in regards to Sarawak cuisine. This field survey was conducted whereby three of each popular local food joints were selected in each of the four districts of Sarawak (Kuching, Sibu, Mukah and Ba'Kalalan) which representative from four categories (customer, cooks, owner of the stalls and representative of professional chefs from Kuching Chefs Association) were selected. Unstructured in- depth interviews conducted with the Chefs, and all data were analysed using content analysis. The results show that almost all of the representatives utilised the same ingredients to prepare the foods and the cooking process and the technique similar from one another. Hence, Sarawak ethnic cuisine the ingredients, cooking process and practice must be accepted and integrated by the peoples. This present study would have an ideal way to prepare the Sarawak ethnic cuisine in the traditional way to maintain the distinctive and yet unique flavour of Sarawak.